Diagnostic vale of serum NSE, and s-100β and inflammatory markers levels in epilepsy : Diagnostic vale of serum NSE, and s-100β - Li, Zhaoxia; Su, Li; Lu, Yi; Hu, Yunqing; Yang, Qian (Journal of Medical Biochemistry, 2025)
Aim:To sodium valproate lore the effects of sodium valproate on serum inflammatory factors and s-100β levels in patients with emergency secondary epilepsy(SE).Methods:This was a retrospective cohort of 120 patients with SE who received Sodium valproate that compared with a group who received carbamazepine regarding different therapeutic drugs. The general data, interleukin (IL)-2, IL-8, tumor necrosis factor (TNF)-α, neuron-specific enolase (NSE), serum acid calcium-binding protein s-100β, total effective rate(TER), seizure onset condition, and adverse reactions (Ars) of the two groups were compared at baseline and at 3 months later. Results:There were no significant differences in age, gender, BMI, course of the disease, stroke type, or seizure type between the study groups (P>0.05). The results showed that IL-2 of the Sodium valproate  group (53.17±4.95 µg/L) was lower versus Carbamazepine group (62.38±4.83 µg/L) (P
Keywords: IL-2, IL-8, TNF-α,serum NSE, and s-100β ,cytokines, secondary epilepsy, sodium valproate